Importance of the teaching – learning strategies to develop the reading and writing skills of English on the students in eighth, ninth and tenth years of basic education at Nueve de Octubre high school in Machala city, during the school year 2013-2014. - Cruz Bernabé, Luis Antonio (2015)
Our research work is performed in the city of Machala, Province El Oro, in the "NUEVE DE OCTUBRE” High School, to analyse the importance of teaching - learning strategies, to develop the reading and writing skills of the English Language in the students of Eighth, Ninth and Tenth Year of Basic Education during the school year 2013-2014, for the purpose of providing the strategies that help a better development and learning this language for the teacher and student. The theoretical framework we have presented in this work focuses on the types of strategies that exist and which could apply to acquire a better understanding and application of a second language, the factors involve in the teaching learning and their influences and how to adapt to achieve in the reading and writings skills. The contextual framework is based on field research conducted in the Education Unit above, in order to observe how important is given to this research within the field of study and how they help in the teaching and learning process in the development of reading and writing skills.